Survey of the Italian monetary situation - CERIANI, L. (PSL Quarterly Review, 2014)
The editorial survey illustrates some banking problems now being much discussed in Italy in view of their reactions on national finance, economic recovery, and the monetary situation. The conclusions of the authors are completed by a brief glance at other important factors affecting the situation. JEL: E50